Surface roughness evaluation of additive manufactured metallic components from white light images captured using a flexible fiberscope. (November 2018) - Haridas, Aswin; Vadakke Matham, Murukeshan; Crivoi, Alexandru; Patinharekandy, Prabhathan; Jen, Tan Ming; Chan, Kelvin
Highlights: Demonstration of light scattering effect on the surface topography of additive manufactured components that are manufactured at various build angles. Comb structures removal (removal of pixelation) from the images acquired using a flexible image fiberscope. Image processing protocol for quantitative roughness characterization using binarized white light images at various thresholds. A parameter, Component Connectivity Exponent based on surface reflectivity is proposed for quantitative roughness characterization. Abstract: The added capabilities of Additive Manufacturing (AM) while processing metallic components have revolutionized the design and manufacturing flexibility of multitudes of aerospace components. However, AM being a stochastic process results in a degraded control of the surface topography of the printed structure and thus requires adequate finishing processes before implementation. Particularly, in the case of components having complex cross-sections and internal channels, none of the currently available technologies offer a solution for the measurement and certification of surface roughness parameters. In this context, this paper investigates a binary image processing technique applied to multiple white light images captured by a 0.3 mm diameter micro fiber endoscope. Further, AM sample surfaces generated by different build angles are investigated to demonstrate the advantages of the proposed technique. A surface roughness evaluation parameter is presented along with measurement results obtained using the Mitutoyo SJ400 (conventional profiler) and the Talyscan 150 (optical profiler).